2018
DOI: 10.1128/iai.00713-17
|View full text |Cite
|
Sign up to set email alerts
|

Brucella abortus Senses the Intracellular Environment through the BvrR/BvrS Two-Component System, Which Allows B. abortus To Adapt to Its Replicative Niche

Abstract: is a facultative extracellular-intracellular pathogen belonging a group of α-Proteobacteria that establishes close interactions with animal cells. This bacterium enters host cells in a membrane bound compartment, avoiding the lysosomal route and reaching the endoplasmic reticulum through the action of the Type IV secretion system, VirB. In this work we demonstrate that the two-component system BvrR/BvrS senses the intracellular environment to mount the transcriptional response required for intracellular life a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 45 publications
1
56
0
2
Order By: Relevance
“…ExoS/ChvI has orthologs in related α-proteobacteria (Vanderlinde and Yost, 2012;Heavner et al, 2015), and orthologs such as BvrS/BvrR in the mammalian pathogen Brucella abortus and ChvG/ChvI in the plant pathogen Agrobacterium tumefaciens are required for virulence (Charles and Nester, 1993;Sola-Landa et al, 1998;Heavner et al, 2015). ChvG/ChvI-dependent transcription is activated by acidic pH and BvrS/BvrR-dependent transcription is activated by acidic pH and nutrient limitation (Yuan et al, 2008;Altamirano-Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…ExoS/ChvI has orthologs in related α-proteobacteria (Vanderlinde and Yost, 2012;Heavner et al, 2015), and orthologs such as BvrS/BvrR in the mammalian pathogen Brucella abortus and ChvG/ChvI in the plant pathogen Agrobacterium tumefaciens are required for virulence (Charles and Nester, 1993;Sola-Landa et al, 1998;Heavner et al, 2015). ChvG/ChvI-dependent transcription is activated by acidic pH and BvrS/BvrR-dependent transcription is activated by acidic pH and nutrient limitation (Yuan et al, 2008;Altamirano-Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many bacterial TCSs, have been involved in intracellular survival mechanisms in eukaryotic cells, such as EvgSA in Shigella flexneri [49]; ArcAB [50], PhoPQ [51] and EnvZ/OmpR [52] in Salmonella thyphimurium ; SrrAB [53]; GraSR [54] in Staphylococcus aureus ; PhoPQ in Escherichia coli [55]; BvrSR in Brucella abortus [56]; and PrrAB in Mycobacterium tuberculosis [57], among others. In S. pneumoniae , most of the TCSs are required for full virulence in animal models of infection [58, 59] and we have shown that two of these systems, StkP/ComE and CiaRH [15, 16], are important in response to acidic and/or oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…У бруцелл описаны растворимые периплазматические белки EipA, EipB наружной мембраны, которые способствуют не только сохранению целостности клеточной оболочки, но и делению бруцелл внутри фагоцитов [31,32].…”
Section: взаимодействие патогена с факторами иммунной системы макроорunclassified